Method for producing silicon carbide coated refractory particles and silicon carbide coated refractory particles

By attached to the use of oxide solidaries on the refractory particles, the silicon carbide coating is attached to the problem of insufficient refractory product performance in existing technologies, and the performance improvement of high -efficiency and economical refractory products is achieved.

CN119343325APending Publication Date: 2025-01-21REFRACTORY INTELLECTUAL PROPERTY GMBH & CO KG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380045684.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-24
Filing Date
2023-08-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively produce refractory products with excellent chemical and physical properties, especially in terms of corrosion resistance and cold compressive strength, and the raw material processing steps are cumbersome and costly.

Method used

By spraying oxide solidaries on the core refractory particles, and mixing with silicon carbide particles in the hybrid equipment, the refractory particles with silicon carbide coating are formed to produce high -quality fire -resistant products.

Benefits of technology

It is possible to significantly improve the corrosion resistance and cold compressive strength of refractory products without adding additional raw material processing steps, and effectively improve product performance through a small amount of silicon carbide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343325A_ABST
    Figure CN119343325A_ABST
Patent Text Reader

Abstract

The invention provides a method for producing silicon carbide coated refractory particles, the method comprising the steps of: a. Providing a core refractory particle; b. Spraying an oxide sol onto the core refractory particles; c. Optionally, mixing the core refractory particles with the oxide sol in a mixing device; d. Adding silicon carbide particles to the core refractory particles; and e. Mixing the mixture obtained in step d to obtain a coated refractory particle having a core and a first silicon carbide coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing refractory particles coated with silicon carbide (SiC) and refractory particles coated with silicon carbide, as well as a batch material for producing a shaped refractory product, and a method for producing a shaped refractory product and a shaped refractory product comprising refractory particles coated with silicon carbide. Background Art

[0002] For the purposes of the present invention, the term "refractory product" refers to a product produced from inorganic refractory raw materials and having a service temperature of more than 600° C. and preferably having a thermometric cone temperature equivalent ("Kegelfallpunkt") of more than 1500° C. according to ISO 836 and DIN 51060. The thermometric cone temperature equivalent ("Kegelfallpunkt") can be determined according to ISO 528 and DIN EN 993-12.

[0003] The raw materials used to produce refractory products are usually based on metal oxides, such as, for example, aluminum oxide ("alumina", Al2O3), magnesium oxide ("magnesia", MgO), silicon dioxide ("silica", SiO2), calcium oxide ("calcia", CaO), zirconium oxide ("zirconia", ZrO2) or chromium oxide ("chromia", Cr2O3). Further common raw materials are based on mixed compounds, such as aluminum silicates (also called "aluminosilicates"), magnesium aluminates (i.e. spinels, preferably stoichiometric spinels with the chemical formula MgAl2O4) or calcium magnesium oxide ("doloma", CaO.MgO). In the present disclosure, “aluminum silicate” refers to a compound based on Al2O3 and SiO2 having a chemical formula of xAl2O3·ySiO2·zH2O, wherein x and y are natural numbers equal to or greater than 1 and z is 0 or a natural number equal to or greater than 1.

[0004] The above mentioned refractory raw materials are usually derived from natural sources, such as naturally occurring minerals, which may be chemically and / or physically treated to obtain the refractory raw materials.

[0005] For example, the main sources of magnesium oxide ("magnesia") are the minerals magnesite (composed of MgCO3) and periclase (composed of MgO). Magnesite is converted to MgO by temperature treatment (e.g., calcination or combustion). Similarly, the main source of calcium magnesium oxide is the mineral dolomite, which can also be converted to the oxide by temperature treatment (e.g., calcination or combustion). Calcium magnesium oxide is also referred to herein as "dolomite lime".

[0006] The main sources of aluminum silicates are the minerals mullite, andalusite, kyanite, sillimanite, and kaolin, as well as refractory clays.

[0007] The main sources of alumina are the natural ore bauxite and the mineral corundum. Bauxite is an aluminum ore that includes a variety of aluminum hydroxide minerals, especially gibbsite (γ-Al(OH)3), boehmite (γ-AlO(OH)) and diaspore (α-AlO(OH)), as well as iron compounds such as hematite (Fe2O3) and goethite (FeO(OH)). Bauxite may also contain a certain amount of kaolin (Al2Si2O5(OH)4), anatase (TiO2), ilmenite (FeTiO3 or FeO·TiO2) and other minerals (such as periclase (MgO). Bauxite is usually calcined to convert aluminum hydroxide into aluminum oxide to obtain a refractory raw material. As used herein, the term "bauxite" refers to calcined bauxite. Typically, the calcined bauxite has an aluminum oxide content of about 75 to 88 wt%.

[0008] By several processing steps, in particular by sintering and / or melting steps and purification steps, refractory raw materials with higher alumina content can also be produced from bauxite. Thus, brown corundum (brown fused alumina), white corundum (brown fused alumina), calcined alumina or plate-like alumina can be obtained. It is known that the refractory products produced by these higher purity alumina raw materials may have chemical and physical properties that are superior to those of products produced by bauxite, for example resulting in improved wear resistance under operating conditions. However, due to the high cost and time-consuming nature of purifying and processing natural minerals, it is desirable to obtain suitable refractory raw materials with as few processing steps as possible.

[0009] It is also desirable to produce high quality refractory products from such refractory raw materials, i.e. refractory products having excellent chemical and physical properties. With regard to chemical properties, it is particularly desirable to achieve high corrosion resistance, since refractory products are often exposed to corrosive compounds, such as those present in slags in steel production. With regard to physical properties, it is particularly desirable to achieve high cold compressive strength (CCS), since CCS is characteristic of products having high mechanical wear stability.

[0010] In order to improve the chemical and physical properties of the final refractory product, high quality raw materials known to produce the desired properties may be blended into the batch used to produce the product.

[0011] In the present disclosure, a "batch" is understood to be a composition of one or more ingredients or raw materials (including additives such as binders) which, by temperature treatment, preferably by tempering (calcination) and / or sintering, can produce a refractory product.

[0012] It is also known that the chemical and physical properties of refractory raw materials can be adjusted by adding coatings to the raw material particles. For example, in WO 2021 / 165300 A1, a zirconium oxide coating is attached to a core particle made of magnesia, magnesite, dolomite or dolomite to improve the elastic properties of the final product. In EP 3868731 A1, a chromium oxide coating is attached to a core particle made of magnesium-chromite, and in EP 3613716 A1, an aluminum oxide coating is attached to a core particle of magnesia. In these prior art documents, an organic liquid, in particular polyvinyl alcohol, is used to attach the coating to the core particle.

[0013] Ren Bo et al. (Ceramics International, vol 43, no. 14, 22.5. 2017, pp. 11048-11057) describe bauxite-SiC refractory materials produced from raw materials containing silica sol-coated light mullite aggregate and SiC aggregate (Sections 2.1 and 2.2). The silica sol-coated light mullite aggregate is used to reduce the thermal conductivity of the product. The coated refractory particles are not further described.

[0014] Sternitzke M. et al. (Journal of the American Ceramic Society, vol. 81, no. 1. January 1998, pp. 41-48) describe the production of alumina / SiC nanocomposites by treating alumina powder with polycarbosilane (PCS) using a titanate coupling agent and then forming silicon carbide from the PCS by pyrolysis. Summary of the invention

[0015] The object of the present invention is to provide a refractory product having excellent chemical and physical properties made from readily available and inexpensive raw materials.

[0016] In particular, the object of the present invention is to provide a refractory raw material that can be used to produce refractory products having excellent chemical and physical properties, in particular in terms of corrosion resistance and parameters such as cold compressive strength, and to provide a method for obtaining such a raw material.

[0017] This object is solved by a method for producing silicon carbide (SiC) coated refractory particles, the method comprising the following steps:

[0018] a. Provide core refractory particles;

[0019] b. spraying the oxide sol onto the core refractory particles;

[0020] c. Optionally, mixing the core refractory particles with the oxide sol in a mixing device;

[0021] d. adding silicon carbide particles to the core refractory particles; and

[0022] e. Mixing the mixture obtained in step d to obtain coated refractory particles having a core and a first silicon carbide coating.

[0023] The object is further solved by a silicon carbide coated refractory particle comprising the following components:

[0024] a. core refractory particles; and

[0025] b. at least one coating layer, wherein the at least one coating layer comprises the following components:

[0026] i. Agglomerates of oxide particles; and

[0027] ii. Silicon carbide particles.

[0028] As used herein, the term "core refractory particle" refers to the refractory raw material particle that is to be coated with silicon carbide.

[0029] The term "sol" is to be understood as a stable mixture of solid colloidal particles in a liquid. An "oxide sol" is to be understood as a sol in which the solid colloidal particles consist of inorganic oxide compounds. The term "colloidal" herein means that the oxide particles are nano-sized and therefore have a size ranging from one nanometer to several hundred nanometers.

[0030] It should be understood that the oxide particles in the oxide sol are smaller than the "particles" described herein, ie, the core refractory particles and the silicon carbide particles.

[0031] The core idea of ​​the present invention is based on the discovery that silicon carbide particles can be attached to core refractory particles using oxide sols to obtain a silicon carbide coating on the core refractory particles. Surprisingly, it has been shown that by attaching (i.e. bonding) silicon carbide particles to core refractory particles using oxide sols, excellent adhesion of the silicon carbide particles to the surface of the core particles can be achieved. This makes it possible to obtain coated particles with unexpectedly thick and uniform silicon carbide coatings, which can be used to produce high-quality refractory products with excellent chemical and physical properties, in particular in terms of their corrosion resistance and parameters such as cold compressive strength.

[0032] Using the present invention, it is possible to obtain coated particles having similar properties to particles made of bulk silicon carbide in terms of chemical and physical properties. Adding these coated particles to a batch material for producing a refractory product enables a high quality refractory product to be obtained without the need to add particles made of bulk silicon carbide to the batch material.

[0033] Since silicon carbide is primarily present in the coating, only a small amount of silicon carbide is needed compared to the total mass of the batch to effectively improve the corrosion resistance of the final product. This is also advantageous considering the limited availability and high cost of silicon carbide.

[0034] The present invention is particularly useful for improving the corrosion resistance and physical properties of lower quality refractory raw material particles, such as refractory raw materials obtained from natural sources with no or only a few processing steps. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A flow chart of a method described herein for producing silicon carbide coated refractory particles is shown.

[0036] Figure 2 An optical microscope image of silicon carbide coated bauxite particles obtained by coating silicon carbide onto core refractory particles of bauxite using silica sol is shown.

[0037] Figure 3 An optical microscope image of silicon carbide coated bauxite particles obtained by coating silicon carbide onto a core refractory particle of bauxite using polyvinyl alcohol is shown.

[0038] Figure 4 The photographs of three sintered refractory bricks after corrosion testing are shown, wherein the refractory bricks were prepared from a batch material in which the coarse particles were white corundum particles ( Figure 4 A), wherein the coarse particles are a batch of uncoated bauxite particles ( Figure 4 B) and a batch wherein the coarse particles are a mixture of silicon carbide coated bauxite particles and uncoated bauxite particles ( Figure 4 C).

[0039] Figure 5 An optical microscope image of silicon carbide coated andalusite particles obtained by coating silicon carbide onto core refractory particles of andalusite using a silica sol is shown. DETAILED DESCRIPTION

[0040] The method according to the present invention comprises steps a to e, which can be performed sequentially or simultaneously (see Figure 1 ).exist Figure 1 In the flowchart of , an arrow with two arrows indicates that the corresponding steps are performed simultaneously (ie, in parallel), while an arrow with one arrow indicates that the corresponding steps are performed sequentially (ie, one after another).

[0041] In step a (see Figure 1 , 100), providing a core refractory particle to be coated. Spraying the oxide sol onto the core refractory particle to wet the core refractory particle with the oxide sol (step b, see Figure 1 , 200). Spraying the oxide sol is particularly advantageous for effectively distributing the sol on the particle surface. The oxide sol can be easily sprayed onto the core refractory particles using a conventional spray gun, and the entire surface of the core refractory particles can be wetted with the oxide sol in an efficient manner. In addition, during or after the oxide sol is sprayed onto the core refractory particles, the core refractory particles can be mixed to further improve the wetting of the core refractory particles by the oxide sol (optional step c, see Figure 1 , 300). For mixing, conventional and / or commercially available mixing equipment can be used. Step b and the optional mixing step c can be carried out either sequentially or simultaneously (see Figure 1 ). Preferably, the optional mixing step c is carried out during the spraying step, ie simultaneously with the spraying step.

[0042] The silicon carbide particles are added to the wetted core refractory particles (step d, see Figure 1 , 400). Figure 1 As shown, step d is preferably performed after step b. In a less preferred embodiment, steps b and d can be performed simultaneously.

[0043] The mixture of the wetted core refractory particles and the silicon carbide particles is mixed so that the silicon carbide particles are attached to the core refractory particles (step e, see Figure 1 , 500). The steps of adding silicon carbide particles and mixing (steps d and e) can be performed sequentially or simultaneously, preferably simultaneously (see Figure 1 ). For mixing (step e), the same mixing equipment as step c can be used. In particular, all steps a to e can be carried out in the same mixing equipment.

[0044] Preferably, steps a, b and d are carried out sequentially, while step c is carried out simultaneously with step b, and step e is carried out simultaneously with step d. Particularly preferably, mixing can be carried out continuously during steps b to e. The present invention enables one or more layers of silicon carbide coating to be attached to the core refractory particles. In this regard, the silicon carbide coated particles obtained from the above steps a to e can be used again as starting material for attaching another silicon carbide coating (see Figure 1 , 600).

[0045] According to one embodiment, the method of the present invention therefore further comprises the following steps:

[0046] f. spraying the oxide sol onto the coated refractory particles;

[0047] g. optionally mixing the coated refractory particles with the oxide sol in a mixing device;

[0048] h. adding additional silicon carbide particles to the coated refractory particles;

[0049] i. mixing the mixture obtained in step h to obtain coated refractory particles having an additional silicon carbide coating; and

[0050] j. Optionally repeating steps f to i one or more times to obtain a coated refractory particle having one or more additional layers of silicon carbide coating.

[0051] By spraying the oxide sol onto the silicon carbide coated refractory particles (step f), the coated particles are wetted with the oxide sol. Optionally, the coated refractory particles are mixed in step g in a similar manner as described in step c above. Silicon carbide particles are added to the wetted coated refractory particles (step h), and the mixture is mixed to allow more silicon carbide particles to attach to the coated refractory particles (step i). Steps f to i can be performed sequentially and simultaneously in a similar manner as described in steps a to e.

[0052] Steps f to i produce a coated refractory particle having another layer of silicon carbide coating, thereby a total of two layers of silicon carbide coating. Optionally, steps f to i can be repeated one or more times to attach additional silicon carbide coatings to the coated particles (step j). The attachment of each layer of silicon carbide coating is also referred to herein as a "coating cycle".

[0053] Preferably one to three coating cycles are performed, for example two coating cycles. Advantageously, by using an oxide sol to attach silicon carbide to the surface of the particles to be coated, a large number of repeated coating cycles can be avoided, since oxide sols enable silicon carbide to attach to the surface very well. Thus, coated refractory particles having a thick and uniform silicon carbide coating can be obtained quickly and easily.

[0054] After the coating cycle is completed, the silicon carbide coated refractory particles may be dried, for example, by storing them at or above room temperature, such as in a drying oven.

[0055] According to the present invention, it is preferred that the silicon carbide particles are significantly smaller than the core refractory particles to ensure that each coated particle has a uniform coating and a similar coating structure.

[0056] Thus, preferably, the core refractory particles have a particle size distribution with a first d50 value and the silicon carbide particles have a particle size distribution with a second d50 value, wherein the first d50 value is at least 50 times higher, preferably at least 100 times higher, more preferably at least 500 times higher than the second d50 value.

[0057] As is well known, the "d50 value" denotes, for a particle mixture, the particle size at which 50% by weight of the particle mixture has a particle size at or below the d50 value and the particle size at which 50% by weight of the particle mixture has a particle size above the d50 value.

[0058] Preferably, the first d50 value, i.e. the d50 value of the core refractory particle, is at least 0.5 mm, preferably at least 1 mm. The d50 value of the core refractory particle can be up to 7 mm. This range of d50 values ​​is preferred because common refractory raw materials are available in these particle sizes. The d50 value of the core refractory particle can be determined using laser diffraction according to ISO 13320-1:2020 and sieve analysis according to DIN EN 1402-3.

[0059] Preferably, the second d50 value, i.e. the d50 value of the silicon carbide particles, ranges from 0.5 to 6 μm. The d50 value range of the silicon carbide particles is preferred because it ensures sufficient size difference with the core refractory particles and enables the use of commercially available silicon carbide particles in the present invention. The d50 value of the silicon carbide particles can be determined using a laser diffraction method according to ISO 13320-1:2020.

[0060] The oxide sol preferably comprises oxide particles having a particle size distribution with a d50 value below 100 nm. Preferably, the d50 value of the oxide particles ranges from 1 nm to 100 nm, even more preferably from 20 nm to 50 nm. A d50 value below 100 nm is beneficial for ensuring that the oxide particles form a colloidal dispersion in the liquid. The d50 value of the oxide particles can be determined using a laser diffraction method according to ISO 13320-1:2020.

[0061] Furthermore, the concentration of the oxide particles in the oxide sol is also selected to achieve a stable colloidal dispersion. Preferably, the oxide sol comprises oxide particles in a concentration of 15 wt% to 60 wt%, preferably 30 wt% to 50 wt%, based on the total weight of the oxide sol. If an oxide sol having an oxide particle concentration in the range of 15 wt% to 60 wt% is used, effective wetting of the core refractory particles and sufficient attachment of the silicon carbide particles to the core refractory particles can be achieved. If the concentration of the oxide particles is lower than 15 wt%, i.e. if the oxide sol contains a large amount of liquid compared to the solid, the attachment of the silicon carbide particles to the core refractory particles may be reduced. If the concentration of the oxide particles is higher than 60 wt%, i.e. the liquid content in the sol is low compared to the solid, the wetting of the core refractory particles may be negatively affected, possibly resulting in the particles not being fully wetted by the oxide sol.

[0062] According to the present invention, the thickness of the silicon carbide coating can be adjusted by adjusting the mass ratio between the core refractory particles and the silicon carbide particles. Preferably, the mass ratio between the core refractory particles and the silicon carbide particles ranges from 70:30 to 99:1, preferably from 80:20 to 95:5. As described above, the total amount of silicon carbide particles can be attached to the core refractory particles in one or more coating cycles. In particular, it has been shown that a small amount of silicon carbide particles relative to the amount of core refractory particles is sufficient to obtain a good coating thickness.

[0063] For example, it has been found that when using core refractory particles having a d50 value of about 1-3 mm and silicon carbide particles having a d50 value of about 2-3 μm, and a mass ratio of core refractory particles to silicon carbide particles of about 85:15 to 90:10, a silicon carbide coating having a thickness of 100 μm or more can be obtained. Such a coating thickness can be obtained in one or two coating cycles.

[0064] The present invention enables coating of a wide variety of core refractory particles with silicon carbide.

[0065] Preferably, the core refractory particles include or consist of at least one of the following: alumina, aluminum silicate, magnesium oxide, magnesium aluminate, calcium oxide, calcium magnesium oxide, silicon dioxide.

[0066] More preferably, the core refractory particles are based on a compound selected from the group consisting of: alumina, aluminum silicate, magnesium oxide, calcium oxide, calcium magnesium oxide and silicon dioxide.

[0067] In this context, the term "based on" means that the particle comprises at least 60 wt.-%, preferably at least 75 wt.-%, even more preferably at least 85 wt.-% of the compound.

[0068] According to a particularly preferred embodiment, the core refractory particles are based on alumina.The core refractory particles based on alumina may be provided in the form of bauxite, brown corundum, white corundum, calcined alumina, platy alumina or corundum.

[0069] Particularly preferably, the core refractory particles are bauxite particles. Generally, it is desirable to prepare refractory products from bauxite because bauxite is a cheap and easily accessible refractory raw material and requires less time and cost to prepare than, for example, preparing brown corundum, white corundum, calcined alumina or tabular alumina. However, it is known that the refractory products made from bauxite are of lower quality than the refractory products made from brown corundum, white corundum, calcined alumina or tabular alumina, especially in terms of their corrosion resistance and physical properties (such as cold compressive strength).

[0070] According to the invention, a silicon carbide coating on bauxite particles can be obtained. The silicon carbide coating significantly improves the chemical and physical properties of the bauxite particles, which is reflected in the improved corrosion resistance and, for example, higher cold compressive strength of the products obtained from a batch based on bauxite and containing bauxite particles coated with silicon carbide compared to the products obtained from a batch based on bauxite without coated particles. Therefore, the invention enables high-quality refractory products to be obtained based on bauxite as raw material, which is not only beneficial for economic reasons, but also enables the widening of the application fields of refractory products based on bauxite.

[0071] Of course, the present invention can also be used to obtain silicon carbide coatings on brown corundum, white corundum, calcined alumina, plate-like alumina or corundum to further improve the chemical and physical properties of these raw materials.

[0072] According to another preferred embodiment, the core refractory particles are based on aluminum silicate, i.e., based on a compound having the chemical formula xAl2O3·ySiO2·zH2O (wherein x and y are natural numbers equal to or greater than 1 and z is 0 or a natural number equal to or greater than 1). The core refractory particles based on aluminum silicate can be provided in the form of mullite, andalusite, kyanite, sillimanite, kaolin or in the form of refractory clay. Like bauxite, these raw materials are both cheap and easy to obtain. In addition, for these materials, it is desirable to be able to adjust their corrosion resistance. Therefore, the present invention enables the acquisition of particles of mullite, andalusite, kyanite, sillimanite, kaolin particles or refractory clay coated with silicon carbide, thereby increasing the possible application areas of refractory products based on aluminum silicate. Preferably, the core refractory particles are andalusite particles (chemical formula: Al2SiO5).

[0073] According to another preferred embodiment, the core refractory particles are based on magnesium oxide. The core refractory particles based on magnesium oxide can be provided, for example, in the form of periclase. Providing magnesium oxide particles (such as periclase) coated with silicon carbide has the advantage of improving the corrosion resistance of the particles. In addition, when added to uncoated MgO particles, SiC-coated MgO particles can act as a resilient and / or toughening agent.

[0074] According to another preferred embodiment, the core refractory particles are based on calcium magnesium oxide.The core refractory particles based on calcium magnesium oxide may be provided in the form of dolomite.

[0075] According to another preferred embodiment, the core refractory particles are based on magnesium aluminate.The core refractory particles based on magnesium aluminate may be provided in the form of spinel.

[0076] The present invention also enables the use of a variety of oxide sols to attach silicon carbide to core refractory particles. The main components of the oxide sol are oxide particles and liquid. The oxide sol may also contain other compounds, such as stabilizers and / or additives (such as surfactants).

[0077] Preferably, the liquid is water, ie, the oxide sol is preferably an aqueous oxide sol. The liquid may also be an alcohol or any other polar organic solvent capable of stabilizing the oxide colloidal particles.

[0078] Preferably, the oxide in the oxide sol is selected from the group consisting of silicon dioxide, magnesium oxide, calcium oxide and aluminum oxide.

[0079] Particularly preferably, the oxide particles consist of silicon dioxide. Preferably, the silicon carbide coating is attached to the core refractory particles using a silica sol (also referred to herein as "silica sol"). It has been found that the use of a silica sol to attach the SiC coating to the core refractory particles enables a particularly thick and uniform SiC coating to be obtained.

[0080] According to a particularly preferred embodiment of the present invention, the core refractory particles are bauxite particles and the oxide sol is a silica sol. This combination is particularly suitable for obtaining a thick and uniform silicon carbide coating on the bauxite particles.

[0081] In other embodiments, it may also be advantageous to select the oxides in the oxide sol to chemically match the chemical composition of the core refractory particles. For example, for core refractory particles based on magnesium oxide, a magnesium oxide sol may be used.

[0082] According to one embodiment of the present invention, the core refractory particles are periclase particles, and the oxide sol is magnesia sol.

[0083] In another aspect, the present invention provides a coated refractory particle produced by the method described herein.

[0084] The coated refractory particles according to the present invention comprise a core refractory particle and at least one coating layer, the coating layer comprising agglomerates of oxide particles and silicon carbide particles. The chemical composition of the core refractory particle may be selected as described above.

[0085] As described herein, the coating particles are produced by attaching a silicon carbide coating to a core refractory particle using an oxide sol. In the coating particles, the liquid in the oxide sol evaporates, and the oxide particles in the sol form oxide particle agglomerates, which are present in the coating. Therefore, "oxide particle agglomerates" should be understood as a plurality of oxide particles originating from the oxide sol sticking together.

[0086] Agglomerates of oxide particles in the coating also serve as "glue" and gap fillers between the silicon carbide particles and the core particles and between the silicon carbide particles.

[0087] The agglomerates of oxide particles are composed of a plurality of individual oxide particles bonded together, and the individual oxide particles preferably have a particle size distribution with a d50 value of 1 nm to 100 nm. The agglomerates may contain, for example, 10 or more than 10, or more than 15, or more than 20 individual oxide particles. The average diameter range of the agglomerates of the oxide particles can be up to 10 μm or more. The coating structure and the average diameter of the oxide particle agglomerates can be analyzed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0088] In the coated refractory particles according to the invention, the majority of said agglomerates of oxide particles are preferably located close to the surface of the core refractory particle (in the case of a first coating layer) or close to the outer surface of a previous coating layer (in the case of a particle having more than one coating layer). Thus, preferably, at least 80% of said agglomerates of oxide particles are located within a first portion of each of said at least one coating layer, said first portion extending to a height of at most 20% of the thickness of each coating layer.

[0089] Preferably, the coated refractory particles according to the present invention are completely coated by said at least one layer of silicon carbide coating. This means that the entire surface of the core refractory particle is preferably covered by silicon carbide.

[0090] As described above, one or more coating cycles may be performed to produce silicon carbide coated particles having one or more coating layers. The sum of the one or more coating layers is also referred to herein as the "silicon carbide coating layer". Preferably, the sum of the thickness of the one or more silicon carbide coating layers averages at least 50 μm. This means that the core refractory particles preferably have a silicon carbide coating layer having an average thickness of at least 50 μm. Preferably, the average thickness of the silicon carbide coating layer is at least 100 μm.

[0091] The average thickness of the silicon carbide coating can be determined by graphical analysis of images obtained by optical microscopy or electron micrographs obtained by SEM or TEM. The average thickness of the coating on a single particle - also referred to herein as "single average coating thickness" - can be determined, for example, by measuring the coating thickness at several locations (preferably at least 5 locations) around the circumference of the particle and then calculating the average.

[0092] The methods described herein will of course produce a plurality of silicon carbide coated refractory particles. If a plurality of silicon carbide coated refractory particles are considered, the overall average coating thickness of the plurality of silicon carbide coated refractory particles can be determined. For example, the overall average coating thickness can be determined by first determining the individual average coating thicknesses of a statistically significant number of individual particles, and then determining the average of the individual average coating thicknesses.

[0093] Preferably, the total average coating thickness of the plurality of silicon carbide coated particles is at least 50 μm. Thus, if a plurality of particles are analyzed, some particles may have individual average coating thicknesses below 50 μm, while other particles may have average coating thicknesses above 50 μm, wherein the total average coating thickness is preferably above 50 μm.

[0094] In yet another aspect, the present invention provides a batch material for producing a shaped refractory product, the batch material comprising silicon carbide coated refractory particles as described herein and a binder, wherein the batch material comprises at least 5 wt%, preferably at least 10 wt% or 20 wt% of the silicon carbide coated refractory particles relative to the total weight of the batch material.

[0095] The batch material may further comprise uncoated refractory particles, preferably the uncoated refractory particles comprise or consist of at least one of the following: aluminum oxide, aluminum hydroxide, aluminum silicate, magnesium oxide, magnesium aluminate, calcium oxide, calcium magnesium oxide, silicon dioxide.

[0096] More preferably, the uncoated refractory particles are based on a compound selected from the group consisting of alumina, aluminum silicate, magnesium oxide, calcium oxide, calcium magnesium oxide and silicon dioxide.

[0097] Preferably, the chemical composition of the uncoated refractory particles corresponds to the core chemical composition of the coated refractory particles. For example, if the core refractory particles are based on alumina, the uncoated refractory particles present in the batch of the present invention may also be based on alumina, and thus, the uncoated particles may be particles of bauxite, brown corundum, white corundum, calcined alumina, platy alumina or corundum, or mixtures thereof.

[0098] According to a particularly preferred embodiment, the coated particles are silicon carbide coated bauxite particles and the uncoated refractory particles are bauxite particles.

[0099] If the core refractory particles are based on aluminum silicate, the uncoated refractory particles present in the batch of the present invention may also be based on aluminum silicate, and thus the uncoated refractory particles may be particles of mullite, andalusite, kyanite, sillimanite, kaolin or refractory clay, or mixtures thereof.

[0100] If the core refractory particles are based on magnesia, the uncoated refractory particles present in the batch of the present invention may also be based on magnesia, and thus the uncoated refractory particles may be periclase particles.

[0101] Of course, the uncoated refractory particles may also have a different chemical composition than the core of the coated refractory particles. For example, the core refractory particles may be bauxite particles, while the uncoated refractory particles are based on aluminum silicate or magnesium oxide.

[0102] The present invention also provides a method for producing a shaped refractory product, comprising the steps of providing a batch material as described herein, and shaping and heat treating the batch material by tempering and / or sintering to produce a shaped refractory product.

[0103] Preferably, the batch material described herein is used to produce shaped refractory products, preferably in the form of ceramic-bonded or carbon-bonded refractory bricks, preferably ceramic-bonded or carbon-bonded non-alkaline refractory bricks. The term "non-alkaline refractory brick" refers to a refractory brick based on non-alkaline raw materials such as alumina or aluminum silicate.

[0104] As is known, "ceramic bonded" refractory bricks are bonded by sintering, ie by firing the green body at a temperature above 1200° C. The batch may contain a binder such as dextrin, which helps to give the green body sufficient strength.

[0105] In the present context, "carbon-bonded" refractory bricks are understood to be refractory bricks which are bonded by carbon bonds. If carbon-bonded refractory bricks are to be produced, the batch material according to the invention further comprises a carbon-based component, for example in the form of graphite, and an organic binder. The organic binder may be in the form of at least one binder known in the prior art, such as bitumen or a synthetic resin. The synthetic resin may be a phenolic resin. In order to produce the carbon-bonded refractory product, the batch material is shaped and tempered, i.e. subjected to a temperature treatment at a temperature preferably below 300°C or 350°C.

[0106] According to one embodiment, the shaped refractory product is a non-basic sintered refractory brick based on alumina or alumina silicate.

[0107] For example, a batch material for producing alumina-based sintered refractory bricks may include bauxite particles coated with silicon carbide in a proportion of 5 to 15 wt% based on the total amount of the batch material, and uncoated particles based on alumina in a proportion of 95 to 80 wt%. The uncoated particles based on alumina may be a mixture of bauxite particles and one or more of brown corundum particles, white corundum particles, calcined alumina particles, plate-like alumina particles, and corundum particles. As a binder, for example, dextrin may be used in an amount of about 1.5 to 3 wt% (e.g., 2 wt%) based on the total mass of the batch material.

[0108] To produce fired bricks, the batch is formed into green compacts and heat treated by sintering. Thus, a formed refractory brick comprising silicon carbide coated refractory particles is obtained. If the sintering step is carried out in a non-reducing atmosphere (e.g. in air), the silicon carbide in the silicon carbide coated refractory particles is at least partially oxidized to silicon dioxide.

[0109] For example, such fired bricks can be used in the glass industry.

[0110] According to another preferred embodiment, the shaped refractory product is a non-alkaline carbon-bonded refractory brick based on aluminium silicate, ie alumina silicon carbide carbon (ASC) brick.

[0111] For example, the batch material for producing ASC bricks may include bauxite particles coated with silicon carbide or silicon carbide coated particles based on aluminum silicate, for example, in a proportion of 10 to 90 wt%, preferably 20 to 60 wt%, based on the total amount of the batch material. The batch material may also contain uncoated particles based on mullite, andalusite, kyanite, sillimanite, kaolin or refractory clay or mixtures thereof (for example, in a proportion of 10 to 90 wt%, preferably 40 to 80 wt%, based on the total mass of the batch material) and a carbon-based component, preferably graphite (for example, in a proportion of 1 to 15 wt%, based on the total mass of the batch material). The batch material may also include silicon carbide particles. As a binder, an organic binder based on a synthetic resin may be used, wherein the binder is present in the batch material in a proportion ranging from 1 to 10 wt%, based on the total mass of the batch material.

[0112] ASC bricks can, for example, be used in the steel industry, for example as lining material for ladle cars.

[0113] In summary, the present invention covers the following embodiments:

[0114] 1. A method for producing silicon carbide coated refractory particles, the method comprising the steps of:

[0115] a. Provide core refractory particles;

[0116] b. spraying the oxide sol onto the core refractory particles;

[0117] c. Optionally, mixing the core refractory particles with the oxide sol in a mixing device;

[0118] d. adding silicon carbide particles to the core refractory particles; and

[0119] e. Mixing the mixture obtained in step d to obtain a coated refractory particle having a core and a first layer of silicon carbide coating.

[0120] 2. The method according to embodiment 1 further comprises the following steps:

[0121] f. spraying the oxide sol onto the coated refractory particles;

[0122] g. Optionally, mixing the coated refractory particles with the oxide sol in a mixing device;

[0123] h. adding more silicon carbide particles to the coated refractory particles;

[0124] i. mixing the mixture obtained in step h to obtain coated refractory particles having another layer of silicon carbide coating; and

[0125] j. Optionally, repeating steps f to i one or more times to obtain a coated refractory particle having one or more additional layers of silicon carbide coating.

[0126] 3. The method according to embodiment 1 or 2, wherein the core refractory particles include or consist of at least one of the following: aluminum oxide, aluminum silicate, magnesium oxide, magnesium aluminate, calcium oxide, calcium magnesium oxide, silicon dioxide.

[0127] 4. The method according to any one of embodiments 1 to 3, wherein the core refractory particles are selected from the group consisting of bauxite particles, mullite particles, andalusite particles, kyanite particles, sillimanite particles, kaolin particles, and refractory clay particles.

[0128] 5. The method according to any one of embodiments 1 to 4, wherein the oxide sol comprises oxide particles consisting of an oxide selected from the group consisting of silicon dioxide, magnesium oxide, calcium oxide and aluminum oxide, preferably consisting of silicon dioxide.

[0129] 6. The method according to any one of embodiments 1 to 5, wherein the core refractory particles are bauxite particles and the oxide sol is a silica sol.

[0130] 7. The method according to any one of embodiments 1 to 6, wherein the core refractory particles are periclase particles and the oxide sol is a magnesia sol.

[0131] 8. The method according to any one of embodiments 1 to 7, wherein the core refractory particles have a particle size distribution with a first d50 value and the silicon carbide particles have a particle size distribution with a second d50 value, wherein the first d50 value is at least 50 times higher, preferably at least 100 times higher, more preferably at least 500 times higher than the second d50 value.

[0132] 9. The method according to any one of embodiments 1 to 8, wherein the first d50 value is at least 0.5 mm, preferably at least 1 mm.

[0133] 10. The method according to any one of embodiments 1 to 9, wherein the second d50 value ranges from 0.5 to 6 μm.

[0134] 11. The method according to any one of embodiments 1 to 10, wherein the oxide sol comprises oxide particles in an amount of at least 15 wt %, based on the total weight of the oxide sol.

[0135] 12. The method according to any one of embodiments 1 to 11, wherein the oxide sol comprises oxide particles having a particle size distribution with a d50 value below 100 nm.

[0136] 13. The method according to any one of embodiments 1 to 12, wherein the mass ratio between the core refractory particles and the silicon carbide particles ranges from 70:30 to 99:1.

[0137] 14. Coated refractory particles produced by the method according to any one of embodiments 1 to 13.

[0138] 15. A silicon carbide coated refractory particle comprising the following components:

[0139] a. having a core refractory particle size distribution having a first d50 value, and

[0140] b. at least one coating layer, wherein the at least one coating layer comprises the following components:

[0141] i. Agglomerates of oxide particles; and

[0142] ii. Silicon carbide particles, wherein the silicon carbide particles have a particle size distribution with a second d50 value, the first d50 value being higher than the second d50 value.

[0143] 16. The silicon carbide coated refractory particle according to embodiment 15, wherein the core refractory particle comprises or consists of at least one of the following: aluminum oxide, aluminum hydroxide, aluminum silicate, magnesium oxide, magnesium aluminate, calcium oxide, calcium magnesium oxide, silicon dioxide.

[0144] 17. The silicon carbide coated refractory particles according to embodiment 15 or 16, wherein the oxide particles consist of at least one of the following: silicon dioxide, magnesium oxide, calcium oxide, aluminum oxide, wherein the oxide particles preferably consist of silicon dioxide.

[0145] 18. The silicon carbide coated refractory particle according to any one of embodiments 15 to 17, wherein the core refractory particle is a bauxite particle and the oxide particle consists of silicon dioxide.

[0146] 19. The silicon carbide coated refractory particle according to any one of embodiments 15 to 18, wherein the core refractory particle is completely coated by the at least one layer of silicon carbide coating.

[0147] 20. The silicon carbide coated refractory particle according to any one of embodiments 15 to 19, wherein the at least one silicon carbide coating has an average thickness of at least 50 μm.

[0148] 21. A silicon carbide coated refractory particle according to any one of embodiments 15 to 20, wherein at least 80% of the agglomerates of the oxide particles are located in a first portion of each of the at least one silicon carbide coating layer, the first portion extending to a height of at most 20% of the thickness of each silicon carbide coating layer.

[0149] 22. A batch material for producing a shaped refractory product, the batch material comprising silicon carbide coated refractory particles and a binder as defined in any one of embodiments 15 to 21, wherein the batch material comprises at least 5 wt%, preferably at least 10 wt% or 20 wt% of the silicon carbide coated refractory particles relative to the total weight of the batch material.

[0150] 23. The batch material according to embodiment 22, further comprising uncoated refractory particles, wherein the uncoated refractory particles include or consist of at least one of the following: aluminum oxide, aluminum hydroxide, aluminum silicate, magnesium oxide, magnesium aluminate, calcium oxide, calcium magnesium oxide, silicon dioxide.

[0151] 24. A method for producing a shaped refractory product, comprising the steps of:

[0152] a. Providing a batch according to embodiment 22 or 23;

[0153] b. shaping and heat treating the batch material by tempering and / or sintering to produce a shaped refractory product.

[0154] 25. A shaped refractory product comprising the silicon carbide coated refractory particles of any one of embodiments 15 to 21.

[0155] The present invention is further illustrated by the following illustrative and non-limiting examples.

[0156] Example

[0157] Example 1: Preparation of silicon carbide coated bauxite particles using silica sol

[0158] Silicon carbide coated bauxite particles were prepared from the starting materials listed in Table 1.

[0159] Table 1: Starting materials used to produce silicon carbide coated bauxite particles

[0160]

[0161] As shown in Table 1, bauxite particles with a particle size of 1-3 mm (d50=2 mm) were used. Of course, larger particles can also be used as starting material, such as bauxite particles with a particle size of 3-5 mm.

[0162] Commercially available silicon carbide particles (SiC particles) having a d50 value of 2.5 μm were used.

[0163] Furthermore, a commercially available silica sol was used, in which the silica particles had a d50 value of 34 nm.

[0164] Silicon carbide coated bauxite particles were prepared in two coating cycles as described in Table 2. Table 2: Silicon carbide coated bauxite particles were prepared in two coating cycles. The proportions of the materials are given in wt. % based on the total mass of the starting materials.

[0165]

[0166] First, bauxite particles were placed in a conventional mixer (total amount of bauxite particles: 8.3 kg), and the mixer was kept running throughout the coating process. The mixer speed was set to 24 rpm. After one minute, silica sol was sprayed into the mixer using a spray gun. After one minute, SiC particles were slowly poured into the mixer. After two minutes, silica sol was sprayed into the mixer. After stirring for another minute, SiC particles were poured into the mixer again. After two minutes, stirring was stopped and bauxite particles coated with silicon carbide were obtained.

[0167] Afterwards, the silicon carbide coated bauxite particles are removed from the mixture and dried at room temperature for one day. Of course, the particles can also be dried at elevated temperatures, such as in a drying oven, which can preferably be operated at a temperature of up to 80°C.

[0168] After drying, the coated particles were analyzed using an optical microscope.For microscopic analysis, the samples were placed in a conventional resin and polished.

[0169] Figure 2 Two optical microscope images of silicon carbide coated bauxite particles obtained as described above are shown. Figure 2 A is an overview image of several coated particles, and Figure 2 B shows a single coated particle (scale bar: 1000 μm). The image shows that the silicon carbide coating is thick and uniform, and the average coating thickness was measured to be about 150 μm.

[0170] Comparative Example 1: Preparation of silicon carbide coated bauxite particles by using polyvinyl alcohol

[0171] Silicon carbide coated bauxite particles were prepared using a similar method as described in Example 1, except that polyvinyl alcohol was used instead of silica sol to attach the silicon carbide particles to the bauxite particles.

[0172] After drying, the coating particles were again analyzed using an optical microscope.

[0173] Figure 3 Two optical microscopy images of silicon carbide coated bauxite particles obtained using polyvinyl alcohol are shown. Figure 3 A is an overview image of several particles, and Figure 3 B shows a single coated particle (scale bar: 1000 μm).

[0174] from Figure 3 A and 3B, it can be seen that the SiC coating is very thin and the particles are not completely coated by SiC.

[0175] In particular, it was observed that if polyvinyl alcohol was used, the silicon carbide particles did not adhere to the surface of the bauxite particles. Instead, the silicon carbide particles tended to "fall off" from the bauxite particles.

[0176] Example 2: Preparation of sintered refractory bricks from batch materials comprising silicon carbide coated bauxite particles Three batch materials as described in Table 3 were provided for the production of sintered (ie, ceramic bonded) refractory bricks:

[0177] Table 3: Composition of Batches 1, 2 and 3

[0178]

[0179] Batch 1 is a batch with white corundum particles as coarse particles, which is an expensive and high-quality alumina raw material. Batch 2 is a batch with uncoated bauxite particles as coarse particles, i.e., a lower-quality alumina raw material. In Batch 3, the coarse particles are a mixture of uncoated bauxite particles and silicon carbide-coated bauxite particles.

[0180] Each batch contains fine particles made of white corundum and dextrin as a binder. The batches also contain chromium oxide to form a chromium alumina phase, which helps improve corrosion resistance. In addition, the batches also contain other compounds, such as agents that promote sintering.

[0181] Each batch was formed into a green body and then sintered at 1500°C for 6 hours.

[0182] For the bricks obtained from batches 1, 2 and 3, the following physical parameters were determined: bulk density, apparent porosity and cold compressive strength (CCS). As can be seen in Table 4, the bricks obtained from batch 3 show similar properties to those obtained from batch 1, while the bricks obtained from batch 2 show significantly lower apparent porosity and CCS. Considering CCS, the bricks produced from batch 3 are even better than those produced from batch 1.

[0183] Table 4: Physical test results of bricks obtained from batches 1, 2 and 3

[0184] Batch 1 Batch 2 Batch 3 Bulk density <![CDATA[g / cm 3 ]]> 3.26 3.11 3.03 Apparent porosity Vol% 17.5 17 17.5 CCS MPa 96.1 79.7 100.2

[0185] The bricks obtained from batches 1, 2 and 3 were further subjected to corrosion tests. For this test, the bricks were first cut into crucibles and a slag obtained from the glass industry (mainly comprising alkali metal salts and sulfates) was placed in them. The samples were then fired at a temperature of 1500° C. for 6 hours.

[0186] The results of the corrosion tests are shown in Figure 4 in the photo. Figure 4 A shows a brick made from Batch 1 after corrosion testing. Figure 4 B shows a brick made from Batch 2 after corrosion testing, and Figure 4 C shows a brick made from Batch 3 after corrosion testing. Figure 4 B It can be seen that the bricks based on batch 2 (uncoated bauxite particles) show large areas of corrosion, whereas the bricks obtained from batch 1 (white corundum particles) and the bricks obtained from batch 3 (a mixture of silicon carbide coated bauxite particles and uncoated bauxite particles) show much less corroded areas. The bricks produced from batches 1 and 3 behave similarly in the corrosion test.

[0187] The above results show that the addition of silicon carbide coated bauxite particles to a batch based on bauxite particles significantly improves the physical and chemical properties of the resulting bricks. In particular, similar or even better properties can be obtained from such a batch when compared to expensive high quality alumina raw materials based on alumina like alumina.

[0188] Thus, replacing batch 1 with batch 3, for example, makes it possible to reduce costs while maintaining or even improving the physical and chemical properties of the produced shaped refractory products.

[0189] Example 3: Preparation of silicon carbide coated andalusite particles using silica sol

[0190] Silicon carbide coated andalusite particles were prepared from the starting materials listed in Table 5.

[0191] Table 5: Starting materials for producing silicon carbide coated andalusite particles

[0192]

[0193]

[0194] Commercially available silicon carbide particles (SiC particles) having a d50 value of 2.5 μm were used.

[0195] Furthermore, a commercially available silica sol was used, in which the silica particles had a d50 value of 34 nm.

[0196] As described in Table 6, silicon carbide coated bauxite particles were prepared in two coating cycles.

[0197] Table 6: Preparation of silicon carbide coated andalusite particles in two coating cycles. The proportions of the materials are given in wt. % based on the total mass of the starting materials.

[0198]

[0199] In general, the silicon carbide coated bauxite particles were mixed and dried as described in Example 1.

[0200] After drying, the coated particles were analyzed using an optical microscope.For microscopic analysis, the samples were placed in a conventional resin and polished.

[0201] Figure 5 Two optical microscope images of silicon carbide coated andalusite particles obtained as described above are shown. Figure 5 A is an overview image of several coated andalusite particles (scale bar: 1000 μm), and Figure 5 B shows a single coated andalusite particle (scale bar: 500 μm). The average coating thickness was determined to be about 100 μm.

Claims

1. A method for producing silicon carbide coated refractory particles, the method comprising the steps of: a. Provide core refractory particles; b. spraying the oxide sol onto the core refractory particles; c. Optionally, mixing the core refractory particles and the oxide sol in a mixing device; d. adding silicon carbide particles to the core refractory particles; and e. Mixing the mixture obtained in step d to obtain coated refractory particles having a core and a first layer of silicon carbide coating.

2. The method according to claim 1, further comprising the steps of: f. spraying the oxide sol onto the coated refractory particles; g. Optionally, mixing the coated refractory particles with the oxide sol in a mixing device; h. adding additional silicon carbide particles to the coated refractory particles; i. mixing the mixture obtained in step h to obtain coated refractory particles having another layer of silicon carbide coating; as well as j. Optionally, repeating steps f to i one or more times to obtain a coated refractory particle having one or more additional layers of silicon carbide coating.

3. The method according to claim 1 or 2, wherein the core refractory particles comprise or consist of at least one of the following: alumina, aluminum silicate, magnesium oxide, magnesium aluminate, calcium oxide, calcium magnesium oxide, silicon dioxide.

4. The method according to any one of claims 1 to 3, wherein the core refractory particles are selected from the group consisting of bauxite particles, mullite particles, andalusite particles, kyanite particles, sillimanite particles, kaolin particles and refractory clay particles.

5. The method according to any one of claims 1 to 4, wherein the oxide sol comprises oxide particles consisting of an oxide selected from the group consisting of silicon dioxide, magnesium oxide, calcium oxide and aluminum oxide, preferably consisting of silicon dioxide.

6. The method according to any one of claims 1 to 5, wherein the core refractory particles are bauxite particles and the oxide sol is a silica sol.

7. The method according to any one of claims 1 to 6, wherein the core refractory particles have a particle size distribution with a first d50 value and the silicon carbide particles have a particle size distribution with a second d50 value, wherein the first d50 value is at least 50 times higher, preferably at least 100 times higher, more preferably at least 500 times higher than the second d50 value.

8. A silicon carbide coated refractory particle comprising the following components: a. a core refractory particle having a particle size distribution of a first d50 value, and b. at least one coating layer, wherein the at least one coating layer comprises the following components: i. Agglomerates of oxide particles, wherein the oxide particles are composed of at least one of: silicon dioxide, magnesium oxide, calcium oxide, aluminum oxide; and ii. Silicon carbide particles, wherein the silicon carbide particles have a particle size distribution with a second d50 value, the first d50 value being higher than the second d50 value.

9. The silicon carbide coated refractory particle of claim 8, wherein the core refractory particle is a bauxite particle and the oxide particle consists of silicon dioxide.

10. A silicon carbide coated refractory particle according to claim 8 or 9, wherein the at least one silicon carbide coating has an average thickness of at least 50 μm.

11. A batch material for producing a shaped refractory product, the batch material comprising silicon carbide coated refractory particles as defined in any one of claims 8 to 10 and a binder, wherein the batch material comprises at least 5 wt%, preferably at least 10 wt% or 20 wt% of the silicon carbide coated refractory particles relative to the total weight of the batch material.

12. The batch material of claim 11, further comprising uncoated refractory particles, wherein the uncoated refractory particles comprise or consist of at least one of: aluminum oxide, aluminum hydroxide, aluminum silicate, magnesium oxide, magnesium aluminate, calcium oxide, calcium magnesium oxide, silicon dioxide.

13. A method for producing a shaped refractory product, comprising the steps of: a. Providing a batch material according to claim 11 or 12; b. shaping and heat treating the batch material by tempering and / or sintering to produce a shaped refractory product.

14. A shaped refractory product comprising silicon carbide coated refractory particles according to any one of claims 8 to 10.

Citation Information

Patent Citations

  • Refractory product, batch for producing the product, process for producing the product and use of the product

    EP3613716A1

  • Grains for the production of a sintered refractory product, a batch for the production of a sintered refractory product, a process for the production of a sintered refractory product and a sintered refractory product

    EP3868731A1

  • Grains for the production of a sintered refractory product, a batch for the production of a sintered refractory product, a process for the production of a sintered refractory product and a sintered refractory product

    WO2021165300A1